3세대 DNA 염기서열 분석과 Hi-C기술을 이용한 꼬막 게놈의 유전체 연구 - 김진무; 이승재; 조은아; 최은경; 조민주; 신소령; 이정식; 박현; Kim, Jinmu; Lee, Seung Jae; Jo, Euna; Choi, Eunkyung; et al. (한국해양생명과학회지, 2021)
Tegillarca granosa, is one of the most important fishery resources throughout Asia. However, due to industrialization factories, marine environmental pollution, and global warming, the marine fishery production has drop sharply. In order to understand the genetic factors of the blood clam, which is a major fishery resource on the southern coast of Korea, the whole genome of blood clam was studied. The assembled genome of T. granosa was 915.4 Mb, and 19 chromosomes were identified. 25,134 genes were identified, and 22,745 genes were functionally annotated. As a result of performing gene gain and loss analysis between the blood clam genome and eight other types of shellfish, it was confirmed that 725 gene groups were expanded, and 479 gene groups were contracted. The homeobox gene cluster of blood clam showed a well-preserved genetic structure within lophotrochozoan ancestor. T. granosa genome showed high similarity between three hemoglobin genes with Scarpharca broughtonii. The blood clam genome will provide information for the genetic and physiological characteristics of blood clam adaptation, evolution, and the development of aquaculture industry. 꼬막은 해양 어업으로써 아시아 전 지역에 있어서 중요한 수산자원 중 하나이다. 하지만, 공장의 산업화, 해양 환경오염, 그리고 지구 온난화로 인해 해양 어업 생산량이 급격히 떨어졌다. 우리나라 남해안의 주요 수산자원인 꼬막의 유전적 특성을 파악하기 위하여 꼬막의 전장유전체를 해독하고 염색체 서열을 규명하였다. 915.4 Mb의 게놈을 조립하였고, 19개의 염색체 유전자 서열을 식별하였다. 꼬막의 유전체에서 25,134개의 유전자들을 확인하였고, 그 중에 22,745개의 유전자들에 대한 기능을 확인했으며, 4,014개의 유전자들에 대한 KEGG pathway를 분석하였다. 꼬막유전체와 8종의 다른 패류와 비교유전체 분석을 통하여 확장/감소(gene gain and loss) 분석을 수행한 결과, 725개의 유전자군의 확장과 479개의 유전자군의 감소를 확인하였다. 꼬막의 homeobox 유전자 클러스터는 촉수담륜동물 내에서 잘 보존된 유전자 구조를 보였다. 또한, 꼬막은 3개의 hemoglobin 유전자들이 피조개의 hemoglobin과 높은 유사성을 보였다. 꼬막의 전장유전체 정보를 통해 꼬막의 환경 적응과 진화의 유전적 특성과 생리적 특성뿐만 아니라, 꼬막 양식의 효율성을 높이는 양식산업에 널리 이용될 수 있는 유전적 정보를 제공할 것이다.